Peran Baitul Maal Wat Tamwil (BMT) NU Cabang Kalibaru Dalam Pemberdayaan Pelaku Usaha Mikro Kecamatan Kalibaru Kabupaten Banyuwangi - Imam Khusnudin; Hasanah Fitri Fatimah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
The purpose of this study is to find out what products are used at BMT NU Kalibaru Branch in empowering micro business actors and to find out how the role of Baitul Maal Wat Tamwil (BMT) NU Kalibaru Branch in empowering micro business actors in Kalibaru District, Banyuwangi Regency. The research method used is descriptive qualitative. Data collection techniques are by means of observation, interviews and documentation. Data analysis tools used with data reduction steps, data presentation, and drawing conclusions. The validity of the data by using source triangulation. The results of this study indicate that the existence of BMT NU Kalibaru Branch provides changes to before financing at BMT NU Kalibaru Branch. In this case, it is proven that the financing provided by BMT NU Kalibaru Branch plays a very important role for micro business actors in terms of capital so that they can increase income for their business. The role of BMT can be seen in the financial, real, and religious sectors, and can be seen from several indicators, namely the fulfillment of capital, improvement and welfare of the community. The conclusion of the study shows that BMT NU Kalibaru Branch in increasing the income and welfare of the community can be seen from the income and increase received by 3 types of businesses after receiving financing from BMT NU Kalibaru Branch there is an increase in the percentage increase from 33% to 80%. After they get financing the average monthly income percentage changes to increase.